Psychosomatic disorders in people with Shereshevsky-Turner syndrome - M. A. Ryznychuk; V. P. Pishak (Kazimierz Wielki University, 2018)
The article deals with topical issues related to the etiology, peculiarities of the phenotypic manifestations of the Shereshevsky-Turner syndrome in different age groups. The incidence of Shereshevsky-Turner syndrome among newborn girls is 1: 2000-1:5000, although some studies mention much more frequent occurrence. An analysis of the features of mental development in patients with partial or complete monosomy was carried out. Patients with Shereshevsky-Turner syndrome should be under a constant supervision of clinical psychologists who are aware of the peculiarities of the disease, and it is also necessary to carefully develop social skills and attitudes in social medium, which will be useful in their further social adaptation.